Suitability of Civic Education Materials in Indonesian Primary Schools for 21st Century Skills - Saputra, Syukron; Rafzan, Rafzan; Taufik, Taufik (Juwara: Jurnal Wawasan dan Aksara, 2025)
The demands of 21st-century education require learning materials that foster critical thinking, creativity and innovation, communication, and collaboration collectively known as the 4Cs. This study aims to examine the extent to which Civic Education (PKn) textbooks used in Indonesian secondary schools align with these essential competencies. Employing a qualitative content analysis approach, the study analyzed three Grade X PKn textbooks published by the Center for Curriculum and Books (Kemendikbud), Erlangga, and Srikandi Empat. The data sources included the textbook content and qualitative feedback from Civic Education teachers and students in Kerinci Regency, Jambi Province. The analysis focused on identifying the presence and integration of 4C elements across chapters, learning activities, and assessment tasks. Findings reveal that the textbooks published by Kemendikbud and Erlangga demonstrate strong alignment with 21st-century skill requirements, particularly in terms of promoting critical thinking, communication, and collaboration. However, creative and innovative skills were less emphasized. In contrast, the textbook from Srikandi Empat displayed limited integration of the 4Cs, indicating the need for further improvement in aligning its content with contemporary educational demands. This study underscores the importance of continuously evaluating textbook quality to ensure their effectiveness as tools for developing students’ future-ready competencies.